Probing the site-specific reactivity and catalytic activity of Ag-n (n=15-20) silver clusters - Anis, Insha; Dar, Mohd Saleem; Bhat, Gulzar Ahmad; Rather, Ghulam Mohammad; Dar, Manzoor Ahmad (ACS Omega, 2022)
Density functional theory calculations within the framework of generalized gradient approximation (GGA), meta-GGA, and local functionals were carried out to investigate the reactivity and catalytic activity of Ag-n (n = 15-20) clusters. Our results reveal that all the Ag-n dusters in this size range, except Ag-20, adsorb O-2 preferably in the bridged mode with enhanced binding energy as compared to the atop mode. The O-2 binding energies range from 0.77 to 0.29 in the bridged mode and from 0.36 to 0.15 eV in the atop mode of O-2 adsorption. The strong binding in the case of the bridged mode of O-2 adsorption is also reflected in the increase in O-O bond distance. Natural bond orbital charge analysis and vibrational frequency calculations reveal that enhanced charge transfer occurs to the O-2 molecule and there is significant red shift in the stretching frequency of O-O bond in the case of the bridged mode of O-2 adsorption on the clusters, thereby confirming the above results. Moreover, the simulated CO oxidation reaction pathways show that the oxidation of the CO molecule is highly facile on Ag-16 and Ag-18 clusters involving small kinetic barriers and higher heats toward CO2 formation.